CHALLENGING CULTURAL APPROPRIATION: PALESTINIAN CULTURAL IDENTITY IN RADHWĀ ‘ĀSYŪR’S NOVEL ATH-THANTHŪRIYYAH - Fitria Utami, Shinta (UIN Raden Mas Said Surakarta, 2023)
This article aims to describe the cultural elements of Palestinian people in Radhwā ‘Āsyūr's novel, ath-Thanthūriyyah, which depicts Palestinian refugees' misery, Palestinian culture, and the struggle to defend Palestinian national identity as experienced by its main character, Ruqayyah. This study uses a literary anthropology perspective through the seven cultural elements defined by Koentjaraningrat. It employs a descriptive-qualitative approach with the data collected in the from words, phrases, sentences, and dialogues in the novel. According to the findings, there are seven elements of Palestinian culture, namely language, knowledge system, technology system, art, religious system, social organization, and livelihood system These cultural elements are presented as a form of resistance to cultural appropriation that happens because of the Israeli occupation.